2014
DOI: 10.1155/2014/734906
|View full text |Cite
|
Sign up to set email alerts
|

Skin Biopsy in the Context of Dermatological Diagnosis: A Retrospective Cohort Study

Abstract: Background. Skin biopsy is an established method for allying the dermatologist in overcoming the diagnostic dilemmas which occur during consultations. However neither do all skin biopsies produce a conclusive diagnosis nor the dermatologists routinely perform this procedure to every patient they consult. The aim of this study was to investigate the favourable clinical diagnoses set by dermatologists when performing skin biopsy, the diagnoses reached by the dermatopathologists after microscopic examination, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
39
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 10 publications
9
39
1
3
Order By: Relevance
“…In a Malaysian experience of 400 biopsies, Yap et al recorded a clinicopathological concordance of 86.8% [7]. In a study of 282 cases, Gupta et al found the same to be 85.8% of the cases, whereas a Greek study found the same to be 68% [5,8]. The clinicopathological concordance in our study was found to be 61.01%.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In a Malaysian experience of 400 biopsies, Yap et al recorded a clinicopathological concordance of 86.8% [7]. In a study of 282 cases, Gupta et al found the same to be 85.8% of the cases, whereas a Greek study found the same to be 68% [5,8]. The clinicopathological concordance in our study was found to be 61.01%.…”
Section: Discussionsupporting
confidence: 63%
“…The histopathological picture depends on a variety of factors that influence the diagnosis; this has been illustrated in various studies. These include the clinical information provided, age of the lesion, technique of the biopsy, and fixation and processing of the tissue amongst others [5].…”
Section: Discussionmentioning
confidence: 99%
“…The skin is the most exposed organ to sunlight and other forms environmental hazards (1) . The management of skin diseases requires an accurate diagnosis, which in many instances constitutes a complex process (2) . Skin biopsy is a fundamental investigation in dermatology, where histopathologic finding assists in determining disease pattern as well as morphological correlations (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Skin biopsies are routinely undertaken in the outpatient dermatology setting as a tool to diagnose benign tumors, malignant cancers, and inflammatory skin lesions. They are the link that allows dermatologists and dermatopathologists to participate in the treatment of patients (3) .Dermatologists often depend on skin biopsy for finalizing their diagnostic abilities (2) . Skin diseases are common and may be the cause of considerable morbidity, especially in elderly (1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation